PENGARUH PROMOTIONAL MIX PADA PENINGKATAN VOLUME PENJUALAN KOSMETIKA SKIVA PT. COSMOLAB PRIMA DI PURWOKERTO - Suwandari, Lusi (Pro Bisnis, 2008)
The objective of the study is to examine the effect of variables promotional mix (advertising, sales promotion and personal selling) to increase sale volume. The entrepreneur or producer will get aid on introducing and explaining their goods and services usage. Promotion can be recognizing market by investigating what is bought by consumer. The hipotesis of the research is the higher cost promotion is the higher production. The result and data used analysis of regresi and correlation revealed two important findings. Firstly, the advertising, sales promotion and personal selling were significantly it have positive and high correlation to increase sale volume. Secondly, advertising is most having an effect on variable to sale volume than sales promotion and personal selling.